Mycoplasma pneumoniae‐associated mucositis – case report and systematic review of literature. (17th February 2014) - Vujic, I.; Shroff, A.; Grzelka, M.; Posch, C.; Monshi, B.; Sanlorenzo, M.; Ortiz‐Urda, S.; Rappersberger, K.
Abstract Background Mycoplasma pneumoniae, a bacterium known to be a common cause of pneumonia, has been documented to cause complications such as debilitating mucositis previously described as an atypical Stevens–Johnson syndrome without skin lesions. However, in the spectrum of epidermal dermatopathies, the condition is increasingly recognized as a separate entity, now termed M. pneumoniae‐associated mucositis (MPAM). Objectives We present a case of MPAM and systemically review the literature to discuss diagnostic and therapeutic options. Methods A systematic literature search was performed to find studies reporting MPAM in adults. We extracted and analysed patient demographics, disease symptomatology, diagnostic testing and treatment. Results Eleven articles, describing 12 patients and our own patient met the predefined criteria and were analysed. Respiratory, ocular and oral symptoms were present in all patients. Therapies predominantly included antibiotics (10 of 13) and immunosuppressive treatment (9 of 13) leading to complete resolution of symptoms in all patients. Conclusion Our findings highlight that MPAM should be recognized as a distinct disease entity within the spectrum of epidermal dermatopathies. We discuss and show in our patient why M. pneumoniae IgA serum levels could prove to be more reliable diagnostic tools in the MPAM diagnosis than the widely used IgG and IgM titre levels.